Victims and the Labour of Justice at the International Criminal Court: the blame cascade - Ullrich, L (Oxford University Press, 2024)
Victim participation at the ICC has routinely been viewed as an empty promise of justice or mere spectacle for audiences in the Global North, providing little material gain for its participants. Why, then, do people in Kenya and Uganda engage in justice processes that offer so little? How and why do they become the court’s victims and intermediaries, and what impact do these labels have on them? Victims and the Labour of Justice at the International Criminal Court offers a response to these poignant questions, demonstrating that the notion of ‘justice for victims’ is not merely symbolic, expressive, or instrumental. On the contrary—the book argues—the ICC’s methods of victim engagement are productive, reproducing the Court as a relevant institution and transforming victims in the Global South into labouring subjects. Challenging the Court’s interplay with global capitalist relationships, the book examines how ‘justice for victims’ is an ideological framework that functions by luring, disciplining, and blaming victims. Drawing on critical theory, criminological analysis, and multi-sited ethnographic fieldwork in The Hague, Kenya, and Uganda, Victims and the Labour of Justice at the International Criminal Court provides an in-depth socio-legal analysis of a key international justice institution. Its analysis illuminates how the drive to include victims as participants in international criminal justice proceedings also creates and disciplines them as highly gendered and racialized subjects.